2017
DOI: 10.1186/s12877-017-0648-4
|View full text |Cite
|
Sign up to set email alerts
|

Social and clinical determinants of preferences and their achievement at the end of life: prospective cohort study of older adults receiving palliative care in three countries

Abstract: BackgroundAchieving choice is proposed as a quality marker. But little is known about what influences preferences especially among older adults. We aimed to determine and compare, across three countries, factors associated with preferences for place of death and treatment, and actual site of death.MethodsWe recruited adults aged ≥65-years from hospital-based multiprofessional palliative care services in London, Dublin, New York, and followed them for >17 months. All services offered consultation on hospital wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 53 publications
7
118
0
2
Order By: Relevance
“…Participating palliative care services in London (England), Dublin (Ireland), New York and San Francisco (USA) were as follows: established hospital palliative care consulting teams in all countries, a hospital-based community outreach team in London and an inpatient palliative care ward in New York. Details of the participating services are found elsewhere [ 19 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participating palliative care services in London (England), Dublin (Ireland), New York and San Francisco (USA) were as follows: established hospital palliative care consulting teams in all countries, a hospital-based community outreach team in London and an inpatient palliative care ward in New York. Details of the participating services are found elsewhere [ 19 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Informal time spent caring was counted with the Client Service Receipt Inventory (CSRI) [ 19 , 23 ], by asking respondents to document all IC time spent by family and friends as well as the respondents during the last 3 months of the patient’s life. Six questions covered a wide range of possible physical, social, emotional and other caring activities, including time spent ‘on call’ and being available for the patient (Additional file 1 : Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Place of death is an important issue to consider for end‐of‐life care. Generally, many patients prefer to stay at home at the end stages of life . Recent studies have shown that dying at home achieves good death in terminally ill cancer patients without increasing caregiver burden .…”
Section: Introductionmentioning
confidence: 99%
“…Surveys and prioritisation research show that most patients with advanced illnesses, regardless of their diagnosis, wish to be cared for and to die at home (Higginson et al . ; Skorstengaard et al . ).…”
Section: Discussionmentioning
confidence: 99%